A bibliometric analysis of studies related to the nuclear factor kappa B signaling pathway in knee osteoarthritis between 2004 and 2023 - Mo, Yafeng; Chu, Jiahao; Chen, Tiewu; Liu, Wenbing; Tang, Jing (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to identify the principal research areas and trends in the nuclear factor kappa B (NF-κB) signaling pathway in knee osteoarthritis (KOA).MethodsThe Web of Science core collection (WoSCC) database was searched for studies related to the NF-κB signaling pathway in KOA published between 2004 and 2023. The complete records of the literature and all citations were exported from the WoSCC database to plain text file and tab-delimited file, respectively. The exported data were then analyzed. Analysis was conducted using CiteSpace (version 1.6.20) and VOSviewer (version 6.1. R6), OriginPro 2021 (version 9.8.0.200), SCImago Graphica (version 1.0.44), and the bibliometric website (http://bibliometric.com/).ResultsA total of 752 studies were included in this analysis, and the results demonstrated an overall increasing trend in the number of published papers and citation frequency over the period 2004−2023. China leads in terms of the number of publications, with 387 publications, followed by the United States (118), and Japan (45). The institutions with the highest number of publications were China Medical University (28) and The Second Affiliated Hospital of Wenzhou Medical University (Yuying Children’s Hospital) (24). The most frequently occurring keywords were “articular cartilage,” “inflammation,” “activation,” and “expression.” Furthermore, recent keywords with high research intensity included “histopathology,” “mesenchymal stem cells,” “subchondral bone,” and “hip.” Toll-like receptor 4 (TLR4), monosodium iodoacetate (MIA), and high-performance anion-exchange chromatography with pulsed amperometric detection (HPAE-PAD) were popular research topics.ConclusionThe bibliometric analysis revealed that studies of NF-κB signaling pathways in KOA have predominantly focused on the TLR4/NF-κB signaling pathway and exosomes. NF-κB plays a core regulatory role in KOA, with molecular evidence supporting its involvement in inflammation, cartilage degradation, and pain signaling. However, current research is limited by the lack of in vivo imaging techniques to visualize NF-κB activity in real-time. Future research should prioritize the development of such imaging modalities and integrate multi-omics approaches, including single-cell and spatial transcriptomics, to analyze pathway heterogeneity and identify novel therapeutic targets. This integrative approach will facilitate a deeper understanding of the pathogenesis of KOA and enable the development of more effective treatment strategies.